A Comprehensive Analysis In Silico of KCS Genes in Maize Revealed Their Potential Role in Response to Abiotic Stress - Xinyi Chen; Aixia Zhang; Chenyan Liu; Muhammad Saeed; Junyi Li; Ying Wu; Yunhao Wu; Haijing Gu; Jinchao Yuan; Baohua Wang; Ping Li; Hui Fang (Plants)
β-ketoacyl-CoA synthase (KCS) enzymes play a pivotal role in plants by catalyzing the first step of very long-chain fatty acid (VLCFA) biosynthesis. This process is crucial for plant development and stress responses. However, the understanding of KCS genes in maize remains limited. In this study, we present a comprehensive analysis of ZmKCS genes, identifying 29 KCS genes that are unevenly distributed across nine maize chromosomes through bioinformatics approaches. These ZmKCS proteins varied in length and molecular weight, suggesting functional diversity. Phylogenetic analysis categorized 182 KCS proteins from seven species into six subgroups, with maize showing a closer evolutionary relationship to other monocots. Collinearity analysis revealed 102 gene pairs between maize and three other monocots, whereas only five gene pairs were identified between maize and three dicots, underscoring the evolutionary divergence of KCS genes between monocotyledonous and dicotyledonous plants. Structural analysis revealed that 20 out of 29 ZmKCS genes are intronless. Subcellular localization prediction and experimental validation suggest that most ZmKCS proteins are likely localized at the plasma membrane, with some also present in mitochondria and chloroplasts. Analysis of the cis-acting elements within the ZmKCS promoters suggested their potential involvement in abiotic stress responses. Notably, expression analysis under abiotic stresses highlighted ZmKCS17 as a potential key gene in the stress response of maize, which presented an over 10-fold decrease in expression under salt and drought stresses within 48 h. This study provides a fundamental understanding of ZmKCS genes, paving the way for further functional characterization and their potential application in maize breeding for enhanced stress tolerance.